Study on Rolling Bearing Life Based on Weibull Distribution and Correlation Coefficient Optimization and Maximum Likelihood Estimation. Issue 1 (1st December 2022) - Liu, Ziyu; Fu, Yongling; Zheng, Shicheng; Wei, Jinkun
Abstract : For the reliability evaluation of rolling bearing life, this paper proposes a parameter estimation method based on the correlation coefficient optimization method and the maximum likelihood estimation method (Cor-MLE), which can obtain more accurate Weibull distribution parameter estimation. Subsequently, the feasibility of Cor-MLE method for Weibull parameter estimation was verified by Monte Carlo simulation data and rolling bearing life test data. Compared with the parameter estimation results of least square method, grey model method and correlation coefficient optimization method, it is proved that the estimation results of this method have high accuracy and can meet the life analysis of rolling bearings.